2023
DOI: 10.1101/2023.08.11.553027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

WOX11-mediated adventitious lateral root formation modulates tolerance of Arabidopsis to cyst nematode infections

Jaap-Jan Willig,
Nina Guarneri,
Thomas van Loon
et al.

Abstract: The transcription factor WUSCHEL-RELATED HOMEOBOX 11 (WOX11) in Arabidopsis initiates the formation of adventitious lateral roots upon mechanical injury in primary roots. Root-invading nematodes also induce de novo root organogenesis leading to excessive root branching, but it is not known if this symptom of disease involves mediation by WOX11 and if it benefits the plant. Here, we show with targeted transcriptional repression and reporter gene analyses in Arabidopsis that the beet cyst nematode Heterodera sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In a previous study, we showed that WOX11 modulates plant tolerance to infections by endoparasitic cyst nematodes (Willig et al, 2023a). Here, we asked whether this also affects nematode parasitism.…”
Section: Wox11 Restricts the Radial Expansion Of Nematode Syncytia An...mentioning
confidence: 91%
See 4 more Smart Citations
“…In a previous study, we showed that WOX11 modulates plant tolerance to infections by endoparasitic cyst nematodes (Willig et al, 2023a). Here, we asked whether this also affects nematode parasitism.…”
Section: Wox11 Restricts the Radial Expansion Of Nematode Syncytia An...mentioning
confidence: 91%
“…At this stage, syncytial elements are symplastically isolated from the surrounding host tissue, which likely enables the build op of turgor pressure required for cellular hypertrophy (Ruan et al, 2004;Hofmann et al, 2007). Since we previously observed that WOX11 and LBD16 are expressed between 2 and 7 dpi (Willig et al, 2023a), we asked whether WOX11 and LBD16 play a role in the early phases of syncytium expansion. To this end, we measured syncytium width in 35S::WOX11-SRDX and lbd16-2 mutants at 5 dpi.…”
Section: Wox11 Restricts the Early Radial Expansion Of Syncytial Elem...mentioning
confidence: 99%
See 3 more Smart Citations